Valoración mediante el flujo de caja descontado y su incidencia en la rentabilidad de la empresa inversiones Mary Dely SAC, de la ciudad de Tarapoto, periodo 2013- 2017 - Navarro Mendoza, Henry Ulises (2013)
This paper considers an investigation based on a descriptive level study, which has as main objective to estimate the value of the company, using discounted cash flow and know their impact on the Return on Company of Inversiones Mary Dely SAC Tarapoto, 2013-2017. To which has formulated the following problem: What is the value and its impact on the profitability of Inversiones Mary Dely SAC, of the city of Tarapoto, period 2013-2017?, For this purpose is considered historical information directly obtained from Inversiones Mary Dely SAC, historical information hardware industry, whose data is decoded and analyzed using tables and graphs, and, through analysis, observation and description of the variables is established the following hypothesis, which, the estimation the value of the company, using the method of discounted cash flow has a positive impact on the profitability of Inversiones Mary Dely SAC, of the city of Tarapoto, 2013-2017. After the phase of analysis and interpretation of the results, the findings must be foremost, the value range obtained by the discounted cash flow is estimated between S/. 228.257 and S/. 761.723, the impact on the profitability of Inversiones Mary Dely SAC, after being valued is positive, since, at the end of 2017, shows a Return on Equity (ROE ) of at least 7.47% in the pessimistic scenario, and 14.61 % maximum in the optimistic scenario . The Return on assets (ROA) at the end of 2017, 10.47% minimum is in the pessimistic scenario and 19.16% at most in the optimistic scenario. The gross profit margin, the year 2017, shows at least 17% in the pessimistic scenario and 19% maximum in the optimistic scenario. The net profit margin at the end of 2017 shows a minimum return of 2.04% in the pessimistic scenario and 4.38 % maximum in the optimistic scenario. Thus the findings show that, management should consider this assessment as a basic element for judgment making future decisions regarding the business, appreciating their value Inversiones Mary Dely SAC in S /. 674,687.00.